Socialization of Strengthening The Pancasila Virtue Movement To UPMI Students - Yusuf Hanafi Pasaribu; Ramadhany Nasution; Ismayani Ismayani; Zetria Erma; Winta Hayati; Yulkarnaini Siregar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Pancasila, as the foundation of the state, plays a vital role in shaping the character of the nation. However, the practice of its values among students has begun to fade due to the challenges of globalization, technological advances, and the influence of foreign ideologies. The problem faced by students at the UPMI in Medan is that their understanding of Pancasila is limited to memorization without appreciation and practice in their daily lives. The phenomena of intolerance, individualistic attitudes, and a decline in social awareness indicate that the internalization of Pancasila values has not been successful. To overcome these problems, activities to promote the Pancasila Virtue Movement were carried out in coordination with the UPMI rectorate and student organizations. The implementation methods included interactive lectures, group discussions, inspirational video screenings, and question and answer sessions. The material covered Pancasila as the foundation of the state and the Pancasila Virtue Movement, the implementation of Pancasila values in student life, and strategies for becoming agents of change. The results of the activity showed an increase in students' understanding of the practice of Pancasila values and the formation of a community of Pancasila-minded students who are committed to carrying out real acts of virtue. This program is expected to strengthen the character of students and make them pioneers of the Pancasila Virtue Movement on campus and in the community.